2014
DOI: 10.1017/s031716710001667x
|View full text |Cite
|
Sign up to set email alerts
|

Referrals, Wait Times and Diagnoses at an Urgent Neurology Clinic over 10 Years

Abstract: Background:An urgent neurology assessment clinic was created at our institution to improve access to prompt neurological assessment, and has been in operation for over a decade. We assessed its timeliness and impact.Methods:The clinic database was examined retrospectively for trends in the volume and waiting time to assessments, neurologic diagnoses, and whether neurologic assessment changed patients’ diagnoses. Before and after implementation, the frequency of emergency department neurology assessments and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The other study reports on a rapid access neurology clinic. 11 A retrospective record review showed that the wait time for an appointment over a 10-year period was 3.8 days. Overall, 44.6% of assessments resulted in a change to the referring diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other study reports on a rapid access neurology clinic. 11 A retrospective record review showed that the wait time for an appointment over a 10-year period was 3.8 days. Overall, 44.6% of assessments resulted in a change to the referring diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,24 Myriad studies, including several described in this discussion, also show that neurology consultation often changes the ED diagnosis within the first day of admission or on rapid follow-up. 11,13,17,[22][23][24][25][26] By providing assurance that the neurology department will arrange for reliable rapid access outpatient appoints, the UCLA Fast Neuro model could enable emergency physicians to more confidently defer care to the outpatient setting, while also providing patients with the most appropriate care for their conditions. Such redirection would reserve resources for true emergencies and inpatient neurologic care for those who need it, while also reducing disparities and improving patient satisfaction and other outcomes.…”
Section: Generalizabilitymentioning
confidence: 99%
“…Nearly one‐third of referrals in neurology are for new‐onset or breakthrough seizures . Neurologists are often provided with the date of a breakthrough seizure or increase in seizure frequency, and asked to determine whether this reflects an actual change in the underlying propensity toward seizures warranting intervention change .…”
Section: Introductionmentioning
confidence: 99%
“…15,8,9 These approaches prioritize testing using measures of varying sensitivity and specificity for the diagnosis of CJD, including magnetic resonance (MR) imaging, 10 electroencephalogram (EEG), 11 and cerebrospinal fluid (CSF) biomarkers (i.e., total-tau, 14-3-3 and real-time quaking-induced conversion [RT-QuIC] 1214 ). The prevalence of specific causes of RPD in a given practice environment are expected to vary with center- (e.g., level of care provided, academic affiliation, referral base 3,7 ), practitioner- (e.g., sub-specialization, clinic wait times 15 ), and patient-specific factors (e.g., age, risk factors and exposures 16,17 ). Accordingly, it remains unclear whether existing approaches are applicable to the diagnosis of RPD in patients assessed in lower-acuity outpatient settings, where the majority of neurological care is delivered.…”
Section: Introductionmentioning
confidence: 99%